Chemical Characteristics of Electron Shuttles Affect Extracellular Electron Transfer: Shewanella decolorationis NTOU1 Simultaneously Exploiting Acetate and Mediators - Li, Shiue-Lin; Wang, Yu-Jie; Chen, Yu-Chun; Liu, Shiu-Mei; Yu, Chang-Ping (Frontiers in Microbiology, 2019)
In the present study, we found that our isolate Shewanella decolorationis NTOU1 is able to degrade acetate under anaerobic condition with concomitant implementation of extracellular electron transfer (EET). With +0.63 V (vs. SHE) poised on the anode, in a 72-h experiment digesting acetate, only 2 mM acetate was consumed, which provides 6% of the electron equivalents derived from the initial substrate mass to support biomass (5%) and current generation (1%). To clarify the effects on EET of the addition of electron-shuttles, riboflavin, anthraquinone-2,6-disulfonate (AQDS), hexaammineruthenium, and hexacyanoferrate were selected to be spiked into the electrochemical cell in four individual experiments. It was found that the mediators with proton-associated characteristics (i.e., riboflavin and AQDS) would not enhance current generation, but the metal-complex mediators (i.e., hexaammineruthenium, and hexacyanoferrate) significantly enhanced current generation as the concentration increased. According to the results of electrochemical analyses, the i-V graphs represent that the catalytic current induced by the primitive electron shuttles started at the onset potential of 0.27 V and continued increasing until +0.73 V. In the riboflavin-addition experiment, the catalytic current initiated at the same potential but rapid saturated beyond 0.07 V; this indicated that the addition of riboflavin affects mediator secretion by S. decolorationis NTOU1. It was also found that the current was eliminated after adding 48 mM N-acetyl-L-methionine (i.e., the cytochrome inhibitor) when using acetate as a substrate, indicating the importance of outer-membrane cytochrome.